Financial Literacy Index and Inclusion of Indonesian Flight Attendant - Abieza, Talitha Rhea; Nainggolan, Yunieta Anny (Journal of Business and Management, 2016)
Abstract. Financial literacy studies are currently being concerned in global financial institutions since it provides contribution to the economic development of a country. However, the study using sample in one particular group that has the similar background is yet limited. This study examines the level of financial literacy and financial inclusion of Indonesian flight attendant, a sample not investigated yet in any literature. Flight attendant is an occupation with the fairly promising salary without any degree requirements that may suggest the needs of financial knowledge to utilize the various financial and investment services to make proper financial decisions. This study aims to: (1) measure Indonesian flight attendant financial literacy level and inclusion using the sample of PT XYZ, (2) examine the determinant of the financial literacy level and inclusion of Indonesian flight attendant, and (3) examine the relationship between the level of financial literacy of Indonesian flight attendant and the demography factors with their financial inclusion. Further, this study also provides suggestions to PT XYZ on how to improve their flight attendant financial literacy and inclusion based on the results of this study. In financial literacy measurement, simple weight factor is employed to determine basic and advance financial literacy weight. Further, regression is employed as the analytical tool to examine: (1) the determinant of demographic factors toward the financial literacy level; and (2) the determinant of demographic factors and financial literacy level toward the financial inclusion. Logistic regression is employed to see the determinant for the possession of investment service and financial adviser. The findings indicate that Indonesian flight attendant have low level of advance and overall financial literacy level. In financial inclusion, the level of financial and investment service possession of Indonesian flight attendant were quite low (except for bank card and credit card). In terms of investment possession and financial adviser possession, the result shows the low percentages that were consistent with the study conducted by The World Bank (2011). Logistic regression shows that both basic and advance financial literacy were significantly associated with the level of investment possession and financial adviser possession. The final OLS regression finds that basic financial literacy has the most significant determinant to the level of financial service inclusion (significant at 1% level). Meanwhile in the investment service inclusion, the highest determinant is the advance financial literacy level (at 1%). Based on the findings, this study suggests PT XYZ to improve their flight attendants’ financial literacy by conducting financial education, since the willingness of financial education of PT XYZ is quite high. For further research, this study could be re-conducted by adding Principal Component Analysis (PCA) to get the more representative result, changing the research object to other professions or other segments, and adding behavioral finance issues to extend the literature.Keywords: Financial Literacy; Financial Inclusion; Financial Education; Indonesian Flight Attendant; Flight Attendant Financial Literacy